Implementation of Multigrid Method for Solving Coupled Problem - Lim, Kean Siang (Universiti Sains Malaysia, 2021)
Coupled problems were systems involving multiple interacting physical systems, were commonplace in nature, making study of it useful. Multigrid methods were algorithms useful for solving multiresolution problems. However, there was a lack of literature on the use of multigrid methods for solving coupled problems. Hence, this project was carried out with the aim of implementing multigrid on coupled problems and studying its performance characteristics. A PETSc example code was modified and used to study the implementation of multigrid for solving a coupled problem. The code was successfully executed to yield a solution. The code was then executed with different solver types and grid sizes to study its performance characteristics. The resulting performance data was plotted to identify the relationship between performance and grid size, and the performance comparison of different solver types. Large grid sizes were found to negatively impact performance of code. The most efficient solver was found from the solvers studied in this project.